Epistemology of Islamic Science: A searching for Ideal Form and Format of Scientific Design for Islamic Higher Education in Indonesia - Iqbal, Moch; Adisel, Adisel (Madania: Jurnal Kajian Keislaman, 2021)
This article is aimed at exploring Islamic science related to the relationship between religion and science which has been being discussed among Indonesian Islamic scientists. Based on the fact occured a long time in many collages under the ministary of religious affair, Islamic educational institutions have only focused on religious science which is narrow and far from science and technology. This research is a type of qualitative research that uses an ex post facto descriptive approach. The descriptive approach is intended to answer questions related to the object under study. Therefore, this is used to systematically describe the present study such as at UIN Sunan Kalijaga Yogkarta, UIN Malang, and UIN Sunan Gunung Djati Bandung. The ex post facto approach is used to evaluate several matters in accordance with the integration and interconnection of science in the three UINs. The results of the study report that first there are several scientific designs that have bring together religion and science. Second, the scientific dichotomy between science and religion is a colonial product that separates religion and science. Third, there is a culmination point between several scientific designs offered by some of these leading Islamic campuses, namely the spirit of reintegration between religion and science which in early Islam did not recognize a scientific dichotomy. Artikel ini bertujuan untuk menggali keilmuan Islam terkait dengan relasi agama dan sains yang masih terus menjadi diskusi di lingkungan ilmuwan Islam Indonesia. Berdasarkan kenyataan yang terjadi di banyak perguruan tinggi di bawah kementerian agama, lembaga pendidikan Islam hanya berfokus pada keilmuan agama yang sempit dan jauh dari ilmu pengetahuan dan teknologi. Penelitian merupakan jenis penelitian kualitatif yang menggunakan pendekatan deskriptif ex post facto. Pendekatan deskriptif dimaksudkan untuk menjawab pertanyaan yang berkaitan dengan objek yang diteliti. Karena itu, dalam hal ini pendekatan deskriptif digunakan untuk menggambarkan secara sistematis objek yang diteliti, yaitu UIN Sunan Kalijaga Yogyakarta, UIN Malang, dan UIN Sunan Gugung Djati Bandung. Pendekatan ex post facto digunakan untuk mengevaluasi beberapa hal yang berkaitan dengan integrasi dan interkoneksi keilmuan di tiga UIN tesebut. Hasil penelitian melaporkan bahwa pertama adanya beberapa desain keilmuan yang mucul yang mempertemukan agama dan sains. Kedua, dikotomi keilmuan antara sains dan agama adalah produk kolonial yang memisahkan antara agama dan sains. Ketiga, terdapat titik temu antara beberapa desain keilmuan yang ditewarkan oleh beberapa kampus Islam terkemuka tersebut, yaitu semangat reintegrasi antara agama dan sains yang memang dalam Islam awal tidak dikenal dikotomi keilmuan.